STUDIES ON THE HELMINTHS INFECTION IN A KURDISH POPULATION IMMIGRATED FROM NORTHERN PART OF IRAQ TO IRAN - J. Massoud (Tehran University of Medical Sciences, 1979)
During 1979-77 a large number of Kurdish populations in northern part of Iraq temporarily immigrated to Iran and settled in Dezful area of Khuzestan province, south-west Iran. Faecal examination of 3,263 samples for intestinal metazoan parasites and 1,154 urine samples for detecting Schistosoma haematobium, infection were performed in different sex and age groups. The percentages of prevalent intestinal helminthes infection were: Ascaril11umbricoides 25%, Trichuris trichiura 16.3%, Hymenolepis nana 14%, Trichostrongylus spp. 2.5% and Hookworm 0.8%. Out of 1,154 urine samples only one infected case of S. haematobium from a 10 ears old male child were detected.